(3CSGSjGJ GdJShjb GdOhGFjs - (3HTjQ(B, (3GdYdGbs ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ(B,s, 2009)
(3jfGbT gPG GdcJGH HCSdhH Sgd heJSdSd CSGSjGJ GdJShjb GdOhGFj, hGSJQGJjLjGJg, hjbOe ddOGQSjjf hGdeeGQSjf eYdheGJ eMOKI, hCSGdjH YedjI, JeJRL ajgG GdfcgI GdYdejI, Yf YGde GdJShjb GdOhGFj hNaGjGg, hafhfg, hCaVd eeGQSGJg(B. (3Efg jJfGhd YfGUQ GdeRjL GdJShjbj GdOhGFj GdCQHYI, hgj GdOhGA hCSGdjH JSYjQg, hJhRjYg, hJQhjLg, HGdEVGaI Edi JhVjM YfGUQ GdHjFI GdcdjI hGdLRFjI GdJj JDKQ Ydi Sdhc GdbGFejf Ydi JbOje GdefJL GdOhGFj, ShGA cGf SdYI, NOeI, Ch acQI(B. (3ceG jJfGhd GdcJGH HGdJaUjd GdCfTWI GdJShjbjI ddUjOdjGJ, hgh aUd Yedj, jcGO jTcd NWhW EQTGOjI ddUjGOdI Jecfge ef COGA CYeGdge, hGdbjGe HfTGWGJge HaGYdjI hcaGjI YGdjJjf(B. (3GdeMJhi UfGYI GdOhGA (B((3eDSSGJgG hNhGUgG hEJLGgGJgG(B) (3GdJShjb GdOhGFj(B:(3CSGSjGJ heaGgje GdHjFI GdJShjbjI GdOhGFjI GdShb GdOhGFjI GdefJLGJ GdOhGFjI GdJQhjL GdOhGFj GdCfTWI GdJShjbjI ddUjOdjGJs
(3HjHdjhZQGajG(B: (3U(B.245 ((3EbJfGAGJ (B2014 3(3f(B)s
Keywords: (3COhjI(B- (3GdJShjbs; (3GdJShjbs; (3GdUjOdIs